Dark volunteerism and knowledge-hiding behaviours: Mediating role of pride - Irum Shahzadi; Muhammad Waseem Bari (South African Journal of Business Management)
Purpose: Using moral licensing theory, this study investigated the relationship between volunteering and knowledge hiding. Moreover, pride (authentic and hubristic pride) is a mediator between volunteering and knowledge-hiding.